Human lachrymal fluid preparation methodology eVol®MEPS – Green analytical approach in clinical and forensic analysis - Renata Wietecha-Posłuszny; Agnieszka Moos-Matysik; Agnieszka Bocheńska (Green Analytical Chemistry)
Eco-friendly and efficient extraction methods are considered as an important area of interest in all analytical procedures. The presented new green approach combines microextraction by packed sorbent (MEPS) with the use of an automated analytical syringe. Ultra-performance liquid chromatography coupled with a sensitive mass spectrometry detector (UHPLC-MS-TOF) was used for simultaneous quantification of benzodiazepines (BZDs) as ‘model’ analytes in human lacrimal fluid (LF). All samples were collected via free spillage on a cheek into disposable test tubes. As the LF samples were only centrifuged prior to the MEPS extraction; the procedure was short, simple and performed with limited sample and solvents consumption.The Vol®MEPS/UHPLC-MS-TOF method was validated. The following parameters were determined: limit of detection (0.01–0.03 ng/ml), limit of quantification (0.03–0.09 ng/ml), linearity (R2>0.99), precision (2.5–12.3 %) and accuracy of the assay (3.3–11.6 %). Based on the example of analysis of a real human sample, it was demonstrated that the method could be a useful tool in forensic and clinical laboratories.